27=6(x-2)

Simple and best practice solution for 27=6(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=6(x-2) equation:


Simplifying
27 = 6(x + -2)

Reorder the terms:
27 = 6(-2 + x)
27 = (-2 * 6 + x * 6)
27 = (-12 + 6x)

Solving
27 = -12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
27 + -6x = -12 + 6x + -6x

Combine like terms: 6x + -6x = 0
27 + -6x = -12 + 0
27 + -6x = -12

Add '-27' to each side of the equation.
27 + -27 + -6x = -12 + -27

Combine like terms: 27 + -27 = 0
0 + -6x = -12 + -27
-6x = -12 + -27

Combine like terms: -12 + -27 = -39
-6x = -39

Divide each side by '-6'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 2(d+1)=-75 | | 8(x-9)-9(x-8)=x+7-(x-1) | | 2x+2=-38-2x | | -1/14-9/14 | | -k+3k+9k+5k=0 | | 5*6+y=20 | | 3(x-1)+2x=19 | | (7n-3)/8=n-1 | | 10x-(4y+8)=-20 | | 7h+5=19 | | 8=11h | | 0=t^2-8t-12 | | f(x)=(x-4)^1/2 | | 8b-6(b-4)=31-5b | | -.75x+8=14 | | 13=25(6x+15) | | -18x^5-10x^2+8x=0 | | 13 = 25(6x+15) | | 9X+4x-7x-5=7 | | -3x+27=6-4x | | 6.8n-32=4.4n+2 | | 2x-10+y=180 | | 82=-8r+90 | | 5x+20=6-2x | | R/8=-24 | | 6q=6(4+1) | | 5x+3(0.05)=4x+7(0.05) | | 240=(l*2)+(20*2) | | 240=(l*2)+(w*2) | | 15.50+x=9.75 | | 4(5x+2)=4(3x+2) | | (12x-7)+(13-4x)= |

Equations solver categories